A Conceptual Model for Promoting Information Security Policy Compliance Behaviour at Workplace - Diman, Allen Peter; T.K.A, Rahman (2024)
Securing sensitive and critical information is a significant challenge for many organisations, as leaks can cause financial, reputational, and competitiveness losses. Organisations can implement an Information Security Policy (ISP) that employees must comply with to minimise this risk. However, ensuring compliance with the ISP continues to be a problem. To address this issue, a conceptual model has been proposed that organisations can use to promote ISP compliance behaviour among their employees. The Health Action Process Approach (HAPA) Model is used to derive this model. The model consists of two phases -motivational and volitional which are expected to cover the elements needed to promote behavioural change for ISP compliance. The model's multi-processes approach, covering critical aspects such as risk assessment, self-efficacy, initiation, and maintenance, enables it to serve as a platform for organisations to sustain ISP compliance over the long term. Organisations can conduct employee assessments and provide ISP compliance training and awareness campaigns to implement the model. They can also disseminate cues about information security issues and how the ISP can assist employees in handling them, discourage behaviour that leads to complacency towards ISP compliance, and update the ISP to keep it relevant. The proposed model presents an opportunity for future research to evaluate its applicability in organisational settings.